The lost jewel of the Atlantic Forest: Kinglet Calyptura Calyptura cristata (Aves: Platyrinchidae) specimen inventory and plumage variation - Silva e Silva, Robson; Pacheco, José Fernando; Schweizer, Manuel; Kirwan, Guy M. (Papéis Avulsos de Zoologia, 2023)
Kinglet Calyptura Calyptura cristata is one of the great enigmas of the South American avifauna. Endemic to an apparently tiny area of south-eastern Brazil, in the Atlantic Forest biome, the species was not definitely seen between sometime in the second third of the 1800s and 1996, when it was briefly rediscovered in submontane forest north-west of Rio de Janeiro. Since then, C. cristata has been reported several times, but without documentation and always by single observers. It is currently considered Critically Endangered by BirdLife International, and various authors have speculated that the species might already be extinct. Given the extreme paucity of knowledge of this species, we provide a complete inventory of museum material for Kinglet Calyptura – more than 100 specimens are listed, the majority held in European collections, almost doubling previous estimates made in the literature. Several are held in relatively small institutions, thereby suggesting that yet more specimens might still be identified or found. In addition, with the benefit of this large sample of material, we discuss morphological variation in the species and we hypothesise particularly about the appearance of male, female and juvenile plumages.